Investigating the Problems of Translating Selected Baghdadi Familial Proverbs: A Cognitive Approach (Al-Mansour Journal, 2024)
Randomly selecting five graduate students majoring in Translation and Interpretation to translate ten Baghdadi culture-specific proverbs into English, the present study aims to highlight difficulties encountered and methods opted for while translating, in addition to measuring to what extent the translations produced succeeded to communicate the intended meaning. The study has shown that translators suffer serious difficulties in dealing with proverbs in translation due to adherence to traditional views of translation theories, lack of necessary cultural awareness in both SL and TL, and keenness to domesticate the translation and thus resulting in the loss of the SL flavor. Concerning methods adopted, the study has shown that there has been fluctuation among three methods; literal translation, paraphrase, and cultural translation. Finally, correctness of translation has been explored, and hence the study has come up with three divisions; correct translation (36%), partially correct translation (i.e. acceptable with reservation) (40%), and false translation (24%).
Keywords: Translation; Baghdadi culture-specific; proverbs